2017
DOI: 10.14716/ijtech.v8i8.733
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanorods Formation for Dye-Sensitized Solar Cells Applications

Abstract: Different morphologies of zinc oxide (ZnO) can be obtained through various synthesizing methods, such as that of the water bath. By synthesizing under various conditions, different ZnO morphologies can be seen as the result of the water bath method. Replacing ZnO nanoparticles with vertically aligned ZnO nanorods results in a much higher energy conversion efficiency. Yet vertically aligned nanorods can only be grown through difficult and expensive methods. Several researchers have studied the growth of one-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The experimental method of this paper was inspired by former work on ZnO NRs by a colleague (Winantyo et al, 2017). Normal glass substrates were cleaned ultrasonically for 5 minutes with distilled water, acetone and ethanol separately.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental method of this paper was inspired by former work on ZnO NRs by a colleague (Winantyo et al, 2017). Normal glass substrates were cleaned ultrasonically for 5 minutes with distilled water, acetone and ethanol separately.…”
Section: Methodsmentioning
confidence: 99%
“…The vertically aligned ZnO nanorods creates more surface defects and oxygen vacancies, have a better photocatalytic efficiency due to their increased specific surface area, which makes the nanorod an effective photocatalyst in photocatalytic applications [13]. By growing vertically oriented ZnO nanorods there is a probability to increase the electron transport rate [14]. Lattice matching of the substrate with ZnO is a key factor for the synthesizing of vertical aligned nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, nanorods possess special characteristics completely different from the bulk ones 13 . Such properties make them suitable for even broader range of applications for instance in: (a) nano-electronics: ZnO nanorods are utilized as extended gate in MOSFET 14 , and logical circuits 15 ; (b) nano-photonics: ZnO nanorod arrays were used as photonic crystals 16 , as light waveguide 17 , as LED 18 , as radiation detector 19 and in dye-sensitized solar cells 20 ; (c) biomedicine: ZnO nanorods and nanoparticles are utilized in biological and biomedical application (diagnosis and therapy) as to possess high radiative efficiency and least toxicity 21,22 ; (d) Spintronics: Magnetic studies showed that Co-doped ZnO nanorods exhibited room-temperature ferromagnetism with a magnetization increasing with Co content 23 ; (e) Gas-sensing: ZnO besides SnO 2 are among the leading materials in gas sensing applications. ZnO nanorods in particular have demonstrated recently very high sensitivity to detect H 2 S at room temperature with a selectivity at the order of ppb 24 ; (f) Bio-sensing: detection of glucose was achieved using ZnO nanorod array 25 .…”
Section: Introductionmentioning
confidence: 99%